Growth, morphology and C/N metabolism responses of a model submersed macrophyte, Vallisneria natans, to various light regimes. (March 2022) - Chen, Jianfeng; Chou, Qingchuan; Ren, Wenjing; Su, Haojie; Zhang, Meng; Cao, Te; Zhu, Tianshun; Ni, Leyi; Liu, Zugen; Xie, Ping
Graphical abstract: Highlights: We continuously monitored the traits of V. natans for 12 months. The increasing function of the ramet number under four light regimes was fitted. C/N metabolism of V. natans was most sensitive to light availability in leaves. The population showed decreased time for reaching the maximal rate of increase in ramet number with increasing light intensity. Abstract: Decreased underwater light availability is one of the most important environmental factors leading to the decline in submersed macrophytes in lakes. However, previous studies mostly focused on a relatively short time scale and lack data on the continuous monitoring of plant life history traits under different light conditions. The present experiment studied the growth, morphology and C/N metabolism of a representative submersed macrophyte, Vallisneria natans, in response to various light regimes (2.8%, 7.1%, 17.1%, and 39.5% ambient light intensity) over a period of 12 months. The results showed that the total biomass and ramet number increased with increased light intensity; in contrast, individual biomass, leaf number and maximum leaf length decreased with increased light intensity. The C/N metabolism indices of V. natans indicated that leaves were the most sensitive to light availability, stems were moderately sensitive, and roots were the least sensitive. V. natans grown in an extremely low-light environment exhibited decreased soluble carbohydrate (SC) and starch and increased free amino acid (FAA) and total nitrogen (TN) levels. The increasing function of the ramet number under different light regimes was fitted. The obtained maximum environmental capacity of the ramet number (K) and the days that the ramet number reached K/2 in each treatment are useful for lake V. natans restoration and seedling cultivation in similar limited-resource environments. Harvesting partial ramets properly and maintaining the ramet number near K/2 could ensure the maximum increase rate of the population to satisfy the demand of V. natans seedlings for lake restoration. The results obtained in this study can be used for lake water level management to achieve specific purposes during submerged macrophyte recovery, such as plant height elongation or plant population quantity expansion.